EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN DEMAM TIFOID DI INSTALASI RAWAT INAP RUMAH SAKIT UMUM CUT MEUTIA ACEH UTARA - Lilik Septiana; Darwin Syamsul; Reza Destri Anggi; Luthvia Luthvia; Rida Evalina Tarigan (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2024)
Typhoid fever is an acute infection of the small intestine which causes digestive disorders and can reduce the level of consciousness. The treatment option in cases of typhoid fever is to use antibiotics. Optimizing the use of antibiotics can be done by monitoring and evaluating the use of antibiotics in hospitals. The aim of this research is to determine the type and rationale for the use of antibiotics in typhoid fever patients at the Cut Mutia General Hospital Inpatient Installation. This research method is non-experimental (observational) research which is analyzed using descriptive methods. The population in this study was all 1423 typhoid fever patients at Cut Meutia General Hospital in 2022-2023. The sample used in this research was 93 respondents using the Slovin formula with purposive sampling technique. Data analysis for this study used quantitative data analysis, namely descriptive analysis. The results of the study showed that the type of antibiotic in typhoid fever patients was mostly the cephalosporin group, namely Ceftriaxon, in 54 patients (58.1%). Evaluation of the use of antibiotics in typhoid fever patients was 100% correct indication, correct patient and drug and 95.7% correct dose. The conclusion of this research is that it is hoped that hospitals will promote the rational use of antibiotics and collaborate with all parties, including hospitals, health professionals and pharmaceutical installations, in preventing antibiotic resistance.